Suppression of Helicobacter pylori infection by daily cranberry intake: A double‐blind, randomized, placebo‐controlled trial. Issue 4 (23rd August 2020) - Li, Zhe‐Xuan; Ma, Jun‐Ling; Guo, Yang; Liu, Wei‐Dong; Li, Ming; Zhang, Lan‐Fu; Zhang, Yang; Zhou, Tong; Zhang, Jing‐Ying; Gao, Ha‐Er; Guo, Xiao‐Ying; Ye, Dong‐Man; et al.
Abstract: Background and aim: Dietary strategies that contribute to reducing incidence of Helicobacter pylori infection without negative side effects are highly desirable owing to worldwide bacterial prevalence and carcinogenesis potential. The aim of this study was to determine dosage effect of daily cranberry consumption on H. pylori suppression over time in infected adults to assess the potential of this complementary management strategy in a region with high gastric cancer risk and high prevalence of H. pylori infection. Methods: This double‐blind, randomized, placebo‐controlled trial on 522 H. pylori ‐positive adults evaluated dose–response effects of proanthocyanidin‐standardized cranberry juice, cranberry powder, or their placebos on suppression of H. pylori at 2 and 8 weeks by 13 C‐urea breath testing and eradication at 45 days post‐intervention. Results: H. pylori ‐negative rates in placebo, low‐proanthocyanidin, medium‐proanthocyanidin, and high‐proanthocyanidin cranberry juice groups at week 2 were 13.24%, 7.58%, 1.49%, and 13.85% and at week 8 were 7.35%, 7.58%, 4.48%, and 20.00%, respectively. Consumption of high‐proanthocyanidin juice twice daily (44 mg proanthocyanidin/240‐mL serving) for 8 weeks resulted in decreased H. pylori infection rate by 20% as compared with other dosages and placebo ( P  < 0.05). Percentage of H. pylori ‐negative participants increased from 2 to 8 weeks in subjects who consumed 44 mg proanthocyanidin/day juice once or twice daily, showing a statistically significant positive trend over time. Encapsulated cranberry powder doses were not significantly effective at either time point. Overall trial compliance was 94.25%. Cranberry juice and powder were well‐tolerated. Conclusions: Twice‐daily consumption of proanthocyanidin‐standardized cranberry juice may help potentiate suppression of H. pylori infection. Trial registration: ChiCTR1800017522, per WHO ICTRP.